2014
DOI: 10.1002/hep.27298
|View full text |Cite
|
Sign up to set email alerts
|

Breadth of neutralization and synergy of clinically relevant human monoclonal antibodies against HCV genotypes 1a, 1b, 2a, 2b, 2c, and 3a

Abstract: Human monoclonal antibodies (HMAbs) with neutralizing capabilities constitute potential immune-based treatments or prophylaxis against hepatitis C virus (HCV). However, lack of cell culture-derived HCV (HCVcc) harboring authentic envelope proteins (E1/E2) has hindered neutralization investigations across genotypes, subtypes, and isolates. We investigated the breadth of neutralization of 10 HMAbs with therapeutic potential against a panel of 16 JFH1-based HCVcc expressing patient-derived Core-NS2 from genotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
76
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 38 publications
13
76
0
Order By: Relevance
“…S1). Of note, IC 50 s measured for H77 HCVcc and S52 HCVcc with bNAbs CBH-5, HC33.4, HC84.26 and AR3A were all consistent with values measured in a previously published study (Carlsen et al, 2014). As has been shown in prior publications (Bailey et al, 2015a;Keck et al, 2009;Wasilewski et al, 2016), relative resistance of HCVcc variants to most bNAbs Table 1, and all neutralization curves are shown in Fig.…”
Section: Agreement Between Hcvcc and Hcvpp Neutralizationsupporting
confidence: 89%
See 1 more Smart Citation
“…S1). Of note, IC 50 s measured for H77 HCVcc and S52 HCVcc with bNAbs CBH-5, HC33.4, HC84.26 and AR3A were all consistent with values measured in a previously published study (Carlsen et al, 2014). As has been shown in prior publications (Bailey et al, 2015a;Keck et al, 2009;Wasilewski et al, 2016), relative resistance of HCVcc variants to most bNAbs Table 1, and all neutralization curves are shown in Fig.…”
Section: Agreement Between Hcvcc and Hcvpp Neutralizationsupporting
confidence: 89%
“…These HCVcc have been used to further define viral entry pathways (Brimacombe et al, 2011;Carlsen et al, 2013;Mathiesen et al, 2015;Timpe et al, 2008) and to show that broadly neutralizing monoclonal antibodies (bNAbs) can prevent HCV infection in animal models (Forns et al, 2000;Morin et al, 2012;Youn et al, 2005). Panels of HCVcc expressing E1E2 from multiple genotypes have also been used to measure neutralizing breadth of bNAbs (Carlsen et al, 2014;Keck et al, 2008Keck et al, , 2013Law et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, we show for the first time that all of these mAbs, except nonneutralizing mAb CBH-4B, segregate into only 3 distinct neutralization clusters. This suggests that resistance polymorphisms outside of known epitopes may confer resistance to many anti-HCV human mAbs, including some of the most broadly neutraliz- neutralization clustering, as it showed synergistic neutralization by a combination of mAbs, HC84.26 and AR4A, which we have identified as NC1 and NC2 mAbs, respectively, in this study (35). Increasing evidence suggests that mutations outside of known binding epitopes may confer resistance to anti-HCV mAbs.…”
Section: Discussionsupporting
confidence: 49%
“…Increasing evidence suggests that mutations outside of known binding epitopes may confer resistance to anti-HCV mAbs. The Carlsen study found no correlation between variation in mapped mAb epitopes and mAb resistance (35). In addition, studies by Keck et al (14) and Fofana et al (36) described mutations arising in single HCV-infected subjects that fell outside of known mAb-binding epitopes and conferred relative resistance to multiple anti-HCV mAbs.…”
Section: Discussionmentioning
confidence: 97%
“…Infusion of bNAbs is protective against infection in animal models of HCV (22, 31), and early high-titer bNAb responses to HCV are associated with viral clearance in humans (3,10,(32)(33)(34)(35). Unfortunately, resistance to bNAbs can also develop, and multiple studies have demonstrated that this resistance sometimes results from mutations distant from bNAb binding sites (11,(36)(37)(38). Since bNAbs may serve as a guide for HCV vaccine development, a more comprehensive understanding of resistance to bNAbs is essential.…”
mentioning
confidence: 99%